PECULIARITIES OF COMMUNICATION IN THE EDUCATIONAL ACTIVITY OF THE MUSEUM - Burceva, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
One of the basic functions of a museum as a cultural institution is education of the society, satisfaction of persons’ aesthetical and cognitive needs. The aim of the article is to find out what aspects of the communication process are related to maintaining the interest of the museum visitors and provision of the availability of information in its educational activity. The research has emphasized the standpoints of museum communication in relation to cooperation partners and users of museum services. The elements of communication described in the research are considered in the context of museum environment. The second part of the article is devoted to the analysis of the results of the empirical research showing the most appropriate ways of getting information for visitors and their satisfaction with the received educational and recreational services in the museum.